Comparison Predominant Oral micro-flora in Subjects with and without Complete Denture Referred to Yazd Dentistry Department - Abbas Ali Jafari; Abbas Fallah Tafti; Ali Fattahi bafghi; Benafshah Arzy (Shahid Sadoughi University of Medical Sciences, 2014)
Introduction: However human oral cavity consist a mass of microorganisms, some alteration such as application the complete removable denture with poor oral hygiene in edentulous patients may cause overgrowth of several opportunistic microorganisms resulted denture stomatitis. The aim of present study was to compare the dominant oral micro-flora between edentulous denture users with dentate elderly. Material and Method: In current analytical, cross-sectional study, 30 edentulous patients with complete removable denture and 30 dentate subjects, who admitted for non-prosthetic treatments, were randomly selected in Yazd dentistry department. Their oral cavity samples were obtained using sterile cotton-tip swabs, for direct smear analyzing and cultivation on the selective fungal as well as bacterial media. Isolated predominant bacteria and fungi were enumerated and identified by microbiological differential diagnosis tests. Data were analyzed with SPSS software with T test and differences were considered statistically significant when p<0.05. Results: The non-aureus staphylococcus and alpha-hemolytic streptococci showed the highest positive culture among the isolated microorganisms in both groups, whereas beta hemolytic streptococci showed the least percent of isolated microorganism in both groups. The higher density of non-aureus Staphylococci, α-hemolitic Streptococci, Gram negative cocobasillus, non-pathogenic Neisseria, Candida and Corynebacterium were recovered from oral samples of denture users in compare with dentate subjects (P= 0.0001). There was also seen a statistical significant correlation between the number of isolated microorganisms and the duration of denture utilization in denture users (P=0.013). Conclusion: Results of the present study showed that complete denture can be act as a predisposal factor in overgrowing of several oral micro-flora particularly Candida, non-aureus Staphylococci, α-hemolytic streptococci, gram negative cocobacillus, non-pathogenic Neisseria, and Corynebacterium, which emphasized the users denture hygine.